289 Dosimetric characterization of a 2D digital mammography (2DDM) unit equipped with narrow-angle and wide-angle digital breast tomosynthesis (DBT). (December 2018) - Della Gala, G.; Ferrari, S.; Filippi, P.; Gavioli, S.; Pomarico, S.; Sassi, S.; Chiesi, M.; Burani, A.; Rivetti, S.
Abstract : Purpose: To perform a dosimetric characterization of a mammographic unit for 2DDM equipped with narrow-angle and wide-angle DBT in a clinical setting. Methods: A retrospective dosimetric characterization was performed on Fujifilm Innovality system for three available modalities: 2DDM, Standard-DBT (DBT-ST, acquisition angle 15°) and High-Resolution DBT (DBT-HR, acquisition angle 40°). All images were obtained with the AEC enabled in normal mode and in a clinical setting between January and May 2017. Both cranio-caudal and mediolateral-oblique views were included in the study. Screening trial patients and patients that already underwent surgery were excluded. For each exam, an automated process obtained the values of compressed breast thickness (CBT) and AGD. AGD was evaluated against CBT. Exponential fitting was performed and compared with calibration curves at various thickness of polymethyl-methacrylate (PMMA). Results: 1561 images of patients receiving 2DDM, 383 DBT-ST and 350 DBT-HR were included in the study. Dosimetric fitting curves showed different trends (Fig. 1). 2DDM and DBT-ST exponential fitting curves (Table 1) were established to be widely lower than achievable dose-limits for 2DDM, especially at high CBT. On the other hand, DBT-HR exponential fitting curve was significantly higher and then very close to acceptable dose-limit for 2DDM, especially at low CBT. For all modalities, although well-known inter-individual variability mainly due to the individual amount of glandular tissue inside the breast, PMMA calibration curves were reliable representation of clinical curves: about 75% of patients' AGD values took place in a neighbourhood ( ± 20%) of the respective calibration curves. Conclusions: Dosimetric characterization of the 2DDM and DBT system was performed, as well as a high level of agreement with the PMMA calibration curves was confirmed. The well-known better performance of wide-angle DBT in terms of vertical axis resolution is paid by a higher AGD with respect to narrow-angle DBT. This suggests the adoption of different DBT modalities to different clinical settings.